The expressions we need to do subtraction with :
[tex] = \tt {2x}^{2} - 11xy + 9 {z}^{2} - {3x}^{2} + 6xy - 4 {z}^{2} [/tex]
Let us now subtract those expression by combining like terms and simplifying them until they can no longer be simplified :
[tex] = \tt - 3 {x}^{2} + 2 {x}^{2} + 9 {z}^{2} - 4 {z}^{2} - 11xy + 6xy[/tex]
[tex] = \tt - 1 {x}^{2} + {5z}^{2} - 5xy[/tex]
Therefore, the answer to :
[tex] \color{hotpink}\tt {2x}^{2} - 11xy + 9 {z}^{2} - {3x}^{2} + 6xy - 4 {z}^{2} \color{plum} = \tt - 1 {x}^{2} + {5z}^{2} - 5xy[/tex]